TIPOLOGI HERMENEUTIKA DAN IMPLEMENTASINYA DALAM TASIR AHKAM ABDUL HALIM BINJAI - Datmi, Muhammad Akbar Rosyidi (El-Waroqoh : Jurnal Ushuluddin dan Filsafat, 2026)
This article examines the typology of hermeneutics and its implementation in the interpretation of legal verses (?y?t al-a?k?m) in the Qur’anic exegesis of Abdul Halim Hasan Binjai. Hermeneutics is often perceived as a foreign approach within Qur’anic studies, while classical Muslim exegetes—particularly those from the Nusantara tradition—are commonly regarded as employing purely textual and normative methods. This study argues that hermeneutical practices have long been embedded in the Islamic exegetical tradition, albeit without explicit theoretical articulation. The purpose of this research is to identify the dominant hermeneutical typology employed by Abdul Halim Hasan Binjai and to analyze how it is implemented in his interpretation of legal verses. This study adopts a qualitative library research method. The primary data are drawn from Abdul Halim Hasan Binjai’s tafsir al-a?k?m, supported by classical and contemporary works on Qur’anic exegesis, Islamic legal theory, and hermeneutics. Data are analyzed using a hermeneutical approach and content analysis to examine patterns of textual interpretation, the relationship between text and context, and the orientation of legal reasoning. The findings reveal that Abdul Halim Hasan Binjai’s tafsir reflects an objective-contextual hermeneutical typology, integrating textual fidelity with contextual considerations and public welfare (ma?la?ah). This study highlights the significant contribution of Nusantara tafsir to the development of Islamic legal hermeneutics. Keywords: Qur’anic hermeneutics, legal exegesis, Abdul Halim Hasan Binjai.